Nutritional and Carrageenan Content of Kappaphycus alvarezii Seaweed Exposed to Ice-Ice - Irmawati, Yuni; Sudirjo, Fien (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
The main source of income for people in Southeast Maluku Regency and Tual City, one of which is the cultivation of Kappaphycus alvarezii seaweed. The problem in cultivating seaweed is when there is an attack of ice-ice disease, which cause a decrease in production yields and quality of K. alvarezii. The target of this research was the nutritional and carrageenan content of K. alvarezii exposed to ice-ice. The parameters observed were nutritional content such as protein, water, ash, fat and carbohydrates as well as carrageenan and gel strenght. The results showed that the nutritional content of K. alvarezii which was exposed to ice-ice, such as 2,01 % protein, 0,14 % fat and 35,74 % carbohydrates, was lower compared to healthy seaweed. However, the water and ash obtained the opposite results, where seaweed exposed to ice-ice was higher, namely 44,66% dan 31,80 %. Carrageenan and gel strenght in healthy seaweed were higher at 58,60 % and 414,86 g/cm2 compared to seaweed exposed to ice-ice, 45,75 % and 404,23 g/cm2.